Aplicação da metodologia de aprendizagem ativa em treinamento com enfoque no lean thinking: proposta de um método para o segmento industrial farmacêutico - Kuo, Chang Chih (2015)
As the market becomes more competitive, more companies strive to improve efficiency and productivity. As a result, waste elimination using techniques and tools based on the approach of Lean Manufacturing focused on Lean Thinking becomes an alternative for companies. In order to achieve this condition, a main step is the development and training of colaborator. In recent years, Active Learning methodology have shown a potential application in training, through methods and techniques that encourage greater interaction of participants in analysis and problems solving listed, and checked application cases in the automotive industry. The objective of this study is to research, evaluate and characterize aspects related to the dynamics of colaborators training of an organization in concepts of Lean Thinking by addressing the Active Learning methodology, preparing a proposal for a method of implementing development training in the segment of pharmaceutical industry. Based on the observations of training with a focus on simulation games, on the applications questionnaires to participants, on the interviews with experts from companies, as well as the use of other techniques of documentary analysis, this work has resulted in a method of training and capacity for the pharmaceutical segment.